Prótesis radífera: Alternativa en el tratamiento de neoplasias de cabeza y cuello - Goiato, Marcelo Coelho [UNESP]; Miyashita, Márcia [UNESP]; Santos, Daniela Micheline dos [UNESP]; Barão, Valentim Adelino Ricardo [UNESP] (My University, 2006)
Radipherpus protheses are a means of treatment for malignant tumor-carrying patients. These protheses are used in cases of brachytherapy or external actinotherapy by contact and allow treating them with high radiation doses that are quickly released from the areas next to tumor, so that the radiations be restricted to the affected region, without the emissions damaging or destroying the soft tissues. Based on these considerations, the present paper was aimed at making literature review on the use of radipherous protheses for the treatment of head and neck neoplasias. © 2006 1995, Editorial Ciencias médicas.
Radipherous protheses, an alternative for the treatment of head and neck neoplasias
Keywords: Brachytherapy; Maxillofacial protheses; Radiation oncology; Radiotherapy